PWE-082 The hepatoma surveillance changes the outcomes?. (17th June 2017) - Rahman, ZU; Ahmed, S; Malde, D; Garcea, G; Delahooke, T
Abstract : Introduction: Hepatocellular Carcinoma (HCC) is the fifth commonest cancer and third leading cause of cancer related deaths 1, 2 . HCC surveillance can diagnose the tumour at an early stage and thus alter the treatment that can be offered. A retrospective analysis was performed of all patients in our region diagnosed with HCC and discussed at our Hepatopancreaticobiliary multidisciplinary team (HPB MDT) over a two year period. Method: Patients with HCC were retrospectively identified from records extending from 1 st October 2014 till 29 th September 2016. Patient information was obtained from the different sources including electronic databases, HPB MDT meeting minutes, clinic letters and patient notes. Standard statistical methods were used. Results: 78 patients with HCC were identified (74%men). The average age was 70 years. Only 32 (41%) patients had or were undergoing treatment at the time of analysis. 46 patients had definite evidence of liver cirrhosis(although poorly documented in the patient notes).Of these only 16 patients were participating, at the time of diagnosis, in HCC surveillance-six monthly imaging and Alpha Fetoprotein (AFP). 11 (69%) of these patients had or were having treatment for HCC.4 had Transarterial Chemoembolization (TACE), 4 had Microwave ablation, 2 had surgical resection and 1 was on Sorafenib. Four of those patients who had ablative treatments were listed for transplantation. Three patients identified by surveillance declined any treatment. In contrast, of 62 patients diagnosed with HCC outside the surveillance, only 21 (34%) patients had or were undergoing treatment. The AFP was found to be normal in 32 (55%) of all patients in whom it was measured at HCC diagnosis. Conclusion: 1) The majority of patients diagnosed in our region with HCC were not participating in HCC surveillance. 2) Those patients undergoing surveillance were more likely to be offered treatment, suggesting identification in the early stage. 3) AFP was normal in the majority of patients with HCC in whom it was tested. References: . The epidemiology of hepatocellular cancer: from the perspectives of public health problem to tumour biology. Caldwell S, Park SH J Gastroenterol 2009;44(Suppl 19):96–101. . Parkin DM. Global cancer statistics in the year 2000. Lancet Oncol. 2001 Sep;2(9):533–43. . Altekruse SF, McGlynn KA, Dickie LA, Kleiner DE, Hepatocellula Carcinoma Confirmation, Treatment, and Survival in Surveillance, Epidemiology, and End Results Registries, 1992–2008. Hepatology 2012;55:476–482. doi:10.1002/hep.24710 Disclosure of Interest: None Declared